2018
DOI: 10.1051/matecconf/201815201009
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Hibiscus Sabdariffa and Jatropha Curcas as Natural Coagulants in the Treatment of Pharmaceutical Wastewater

Abstract: Abstract. Pharmaceutical wastewater is one of the most difficult wastewater to treat due to the presence of pharmaceutical compounds resulting in high concentration of organic matter, high turbidity and Chemical Oxygen Demand (COD). Chemical-based coagulation is a common method used to treat wastewater. However, the issue that has been raised with the use of chemical coagulants is their presence in water after treatment that can cause risks to the human health such as Alzheimer and cancer. Natural coagulants c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 13 publications
2
15
0
Order By: Relevance
“…The seeds of H. Sabdariffa show its best performance removing contaminants in greywater at 100 mg/L of H. Sabdariffa [20]. In addition, when H. Sabdariffa used to treat pharmaceutical wastewater, its optimum dosage is 190 mg/l [19]. However, due to the variance of the characteristic of greywater collected, the results may be similar or slightly different from previous study.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The seeds of H. Sabdariffa show its best performance removing contaminants in greywater at 100 mg/L of H. Sabdariffa [20]. In addition, when H. Sabdariffa used to treat pharmaceutical wastewater, its optimum dosage is 190 mg/l [19]. However, due to the variance of the characteristic of greywater collected, the results may be similar or slightly different from previous study.…”
Section: Introductionmentioning
confidence: 91%
“…Hibiscus Sabdariffa is commonly used to produce foods, herbal drinks and flavouring agents from its flower [19]. Its seeds are waste and discarded in these industries.…”
Section: Introductionmentioning
confidence: 99%
“…Sibartie and Ismail [84] studied the performance of H. Sabdariffa and J. Curcas as a neutral coagulant for pharmaceutical wastewater treatment. The results demonstrate that at a coagulant dosage of 190 mg/L and pH 4, the maximum removal efficiency was achieved for turbidity (5.8%) and COD (30%) by H. Sabdariffa, while J. Curcas works best at pH 3 and a coagulant dosage of 200 mg/L to remove 51% of turbidity and 32% of COD.…”
Section: Application Of Natural Coagulants For Pharmaceutical Removalmentioning
confidence: 99%
“…From the previous studies of natural coagulant, most of the optimum slow mixing speed are at 30 to 40 rpm [19][22] [35] due to the performance of turbidity, COD and TSS removal. In this study, it has shown that the slow mixing speed for Artocarpus Heterophyllus seeds is at 20 rpm.…”
Section: Effect Of Mixing Speedmentioning
confidence: 99%